On reconstructibility of switched Boolean control networks. Issue 12 (2nd December 2021) - Gao, Zhe; Feng, Jun-e; Wang, Biao
Abstract : This paper investigates the reconstructibility of switched Boolean control networks. Reconstructibility is the ability to determine the current state based on the known data. Four types of reconstructibility are proposed for the first time. Two methods for studying reconstructibility are provided. One method is to compare the periodic state-model-input trajectories with the same period and the other is to construct the distinguishing matrix, which can describe all initial states and their corresponding outputs driven by different model-input sequences. By virtue of them, several conditions to determine four types of reconstructibility are obtained. Finally, a state observer is designed and two examples are given to illustrate the effectiveness of obtained results.